2008
DOI: 10.1073/pnas.0711566105
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study shows BCL11A associated with persistent fetal hemoglobin and amelioration of the phenotype of β-thalassemia

Abstract: ␤-Thalassemia and sickle cell disease both display a great deal of phenotypic heterogeneity, despite being generally thought of as simple Mendelian diseases. The reasons for this are not well understood, although the level of fetal hemoglobin (HbF) is one well characterized ameliorating factor in both of these conditions. To better understand the genetic basis of this heterogeneity, we carried out genome-wide scans with 362,129 common SNPs on 4,305 Sardinians to look for genetic linkage and association with Hb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
513
3
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 599 publications
(537 citation statements)
references
References 38 publications
15
513
3
6
Order By: Relevance
“…More recently, the technique of genome wide association studies (GWAS) has been used to confirm the importance of 2 previously identified loci. One of these is the BCL11A intron 2 polymorphism at chromosome 2p16, and the other is the HBS1L-MYB intergenic polymorphism at chromosome 6q23 [24]. The advantage of genome wide association studies is that it enables pinpointing the specific gene involved more precisely than linkage studies and furthermore, this methodology can potentially reveal associations which were not previously revealed using linkage.…”
Section: Genetic Modifiersmentioning
confidence: 99%
“…More recently, the technique of genome wide association studies (GWAS) has been used to confirm the importance of 2 previously identified loci. One of these is the BCL11A intron 2 polymorphism at chromosome 2p16, and the other is the HBS1L-MYB intergenic polymorphism at chromosome 6q23 [24]. The advantage of genome wide association studies is that it enables pinpointing the specific gene involved more precisely than linkage studies and furthermore, this methodology can potentially reveal associations which were not previously revealed using linkage.…”
Section: Genetic Modifiersmentioning
confidence: 99%
“…The association of SNP alleles with HbF levels was evaluated by linear regression, with age and sex as covariates. Association was also tested with a joint 'SNP score' (22). Allele frequencies between populations were compared using chi-square test.…”
Section: Resultsmentioning
confidence: 99%
“…These observations have been confirmed through the analysis of single nucleotide polymorphisms at the level of the 2p15 locus and F-cell production in a population of Sardinian β-thalassemic patients. Particularly, it was observed that the SNP rs11886868 variant is significantly associated with Hb [39].…”
Section: Regulation Of γ-Globin Gene Expressionmentioning
confidence: 99%